Predicting Financial Distress and Financial Performance Analysis of PT Bayan Resources Tbk. - Putranto Wicaksono, Adhi; Maya Damayanti, Sylviana (The Indonesian Journal of Business Administration, 2016)
Abstract. PT Bayan Resources Tbk. is a producer of environmentally friendly low sulfur, sub-bituminous and semi-soft coking coals integrating coal mining, processing and logistic operations. Since established. PT Bayan Resource Tbk. Continuously expand its business by acquiring a number of new coal concessions. In the past 3 years PT Bayan Resource Tbk net profit is decreased drastically and even suffer loss in the fiscal 2013 and 2014. Based on probability of default analysis using Altman Z-score bankruptcy model, PT Bayan Resources Tbk in 2014 they already in the â€œDistressâ€ zone (Zâ€™ < 1.23). If PT Bayan Resources Tbk performances keep declining, they will facing in financial difficulties and will bankrupt in the future. This study proposes four business solution to mitigate the current problem. Which are reducing the stripping ratio to reducing the cost of production, increase the domestic market share by improving the marketing and external relation so they can get the tender to increase selling coal in Indonesia and to increase the revenue, cost Efficiency by improving the mining equipment utility and technology and also by using differentiation strategy, which is, build a new power plant to get the revenue not only from selling coal, but from selling the electricity to PLN or another entity.Â Keyword: Coal Mining, Financial Distress, Business Strategy, Financial Performance, Financial Analysi